LET’S TALK ABOUT A REVISED RACE-BASED CURRICULUM (EDUCATION IN THE 21ST CENTURY, 2025)
Why is this paper needed? There are many reasons why this paper is not just needed but should be required, essential reading to create the critical consciousness (Freire 2021) and conceptual baseline for a transformative, multimodal, multiliterate, decolonized curriculum to effect change. The paper is derived from the researchers’ previous work on formative pedagogical models and curriculum development and their observations, analysis, and development of race-based curriculum models (Charles 2019). The authors address the core of that process, the requirement for an evidenced presentation to policy makers of the need for a race-based curriculum and its conceptual foundation. Content change requires a paradigmatic shift in its function and worldview (Mazama, 2003), where knowledge can never be produced for the sake of it, a paradigm must activate our consciousness to be of any use to us (ibid, p.3)
Keywords: race-based curriculum; decolonization of education; critical pedagogy; Afrocentric paradigm; formative assessment; inclusive education; multiculturalism; educational equity